Novel technologies for developing cadmium tolerance - Alves, Ritade Cássia [UNESP]; Alves, Letícia Rodrigues [UNESP]; Checchio, Mirela Vantini [UNESP]; Nicolau, Mayara Cristina Malvas [UNESP]; Prado, Emilaineda Rocha [UNESP]; Gratão, Priscila Lupino [UNESP] (Elsevier, 2019)
Although many questions concerning reactive oxygen species metabolism and cadmium (Cd) have not been answered, the rapid progress of proteomics and metabolomics, and their interactions, may be important tools in helping to define these roles more clearly in the near future. In addition, metabolomics can provide biochemical and physiological knowledge about network organizations in plants subjected to Cd stress. Understanding these processes may considerably increase our knowledge of Cd phytotoxicity and induced oxidative stress. Such information, complemented by using mutants, genetic engineering, and the development of cellular markers, will allow the manipulation of cellular redox status and identify traits for plant tolerance programs.
Keywords: Cadmium; Cellular markers; Metabolomics; Mutants; Oxidative stress; Phytotoxicity; Redox status; Tolerance